The design and fabricate a pulse shape discriminator apply signal processing method using EJ-301 detector - Dang Hong , Ngoc Quy; Pham, Ngoc Tuan; Tuong Thi, Thu Huong; Phan, Van Chuan; Nguyen, Nhi Dien (Nuclear Science and Technology, 2017)
The high quality measurements of neutron energy spectra are required in various fields of research and applications. However, in many cases the contribution of gamma background causes the inaccuracy of neutron spectrum. Therefore, the discrimination of gamma-ray events in neutron spectrum is necessary. In this article, an algorithm for digital implementation of the chargecomparison method for n/γ discrimination based on Digital Signal Processing technique is described. Furthermore, the APX-500 board was used as a hardware for the development of a Pulse Shape Disciminator, and is equipped with ADC ADM-414 14 bit-100 MSPS. The fully system has been tested with EJ-301 detector, using 252Cf neutron source.